Preventing Man in The Middle Attack on E-voting System Using Multi-layer Security Protocol - Uzoma Sunday (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2025)
The rapid expansion of the Internet has revolutionized e-voting, offering unparalleled convenience for voters. However, this growth introduces critical security vulnerabilities, particularly Man-in-the-Middle (MITM) and phishing attacks. To address these threats, this study presents a secure Android-based e-voting application developed using the Software Development Life Cycle (SDLC) methodology. The proposed system integrates a robust five-layer security protocol encompassing user authentication, fingerprint recognition, CAPTCHA, One-Time Password (OTP) verification, and cryptographic encryption. By mitigating MITM attacks, this multi-layered approach ensures secure, remote ballot casting. The outcome of this research is a reliable mobile platform that successfully safeguards voter privacy and election integrity against modern cyber threats